Features of plant communities of natural forage lands of Talas river delta (Experimental biology, 2016)
Pasture is not only the place used in agriculture for herding cattle; its development is associated with the prosperity of cattle breeding, as well as the improvement of the welfare. The improvement of pasture infrastructures, preventing degradation of pastures, preservation of ecological integrity of pasture ecosystems in the environment is one of the most pressing issues of today.The article describes and defines the floristic composition of plant communities of natural forage lands of Talas River delta, Zhambyl Region. Talas River flows through the lands of Bayzak, Talas, and Sarysu Districts. The study was conducted in Kenes and Shakirov rural districts of Talas District.  The study revealed 97species belonging to 65 genera and 22 families in the floristic composition of the vegetation cover of Kenes and Shakirov rural districts. Top 5 in the number of dominant species includes Chenopodiaceae Vent, Poaceae Barn, AsteraceaeBercht, Fabaceae Lindl, and Liliaceae Hall families. Such families as Plumbaginaceae Juss, Zygophyllaceae R.BR, Cruciferae Juss, Cyperaceae Juss., Caryophyllaceae Juss, and Iridaceae Juss are represented by 1-4 species.Ecological analysis of the local flora of the survey district shows the widespread of xerophytes on piedmont plain, mesophytes and halophytes – in the depressions and ancient alluvial delta of the Talas River.The communities are dominated by Artemisia terrae-albae Krasch.  Salsola arbuscula eformis Drob., Salsola orientalis S.G. Gmel. However, the intensive use of the area for grazing in the recent past has increased the grazing area with secondary vegetation. Such pastures are dominated by annual Salsolas and Geratocarpus (G.arenarius L. and G. utriculosus Bluk) which displace the food plants (A.terrae-albae, Alhagi kirghisorum Schrenk., Aeluropus intermedius Rgl.). Perennial cultures are replaced with grazed annual Salsolas with lower crop which has sharp fluctuations from year to year and season to season. This process represents a dangerous degree of pasture degradation.On piedmont plains, there are islets of undulating sands dominated by Calligonum aphyllum (Pall.) Guerke and A.terrae-albae pastures. The depressions of the piedmont plain are covered with pastures dominated by A.intermedius and sub-dominated by Climaсoptera brachiata (Pall.) Botsch. Ancient alluvial delta of the Talas River has mosaic vegetation richer in species than the piedmont plain. Most of the pastures are covered by A.kirghisorum, assisted with A.annectent and C.brachiata.The comparison of results of the surveys of 1978 and 2015 revealed some changes in vegetation, mainly related to the dynamics of the weather, environmental conditions, specification of plant species and the maintenance of separate circuits.
Keywords: vegetation; pasture; hay; floristic composition; dominant species; plant families.